An Enquiry into Learners' Disengagement from Schooling-South African Secondary Schools: Teachers' Perspective - Ahmed, Nadeem (CV Sinergi Ilmu dan Publikasi, 2025)
Learners’ disengagement from schooling exhibit behaviors that evade being on track for learning, resulting in learners’ lower academic performance, and a serious concern of South African secondary schools. The high probability of learners’ disengagement from schooling (45%) in South Africa is not only a concern for learners, teachers, and schools but it is also a concern for a family and society. Thus, the research intends to examine the factors associated with learners’ disengagement from schooling at secondary schools. The research employed a generic qualitative research approach. A total of eighteen teachers from six secondary schools were selected to undertake the research by employing a purposive sampling technique. It was identified that multiple factors play a negative role which leads learners to disengage from schooling. Disengagement negatively impacts learners’ academic achievement and results in low performance. Low-performer learners have behavioral and social issues with peers and long-term negative effects on their future lives. Moreover, disengaged learners have more probability of being involved in drug abuse and have a higher risk of dropping out of school. During the research, it was found that poverty and socio-economic background, teenage pregnancies, drug abuse, and broken family structure are some of the major challenges that South African society faces and are the main factors that influence learners’ disengagement from schooling. The schools that choose to accomplish the research deal with learners from diverse backgrounds. Learners from these backgrounds cannot engage themselves with schooling because of the shortage of essential educational resources, and lack of motivation and guidance from parents. It is hence mandatory for the parents, teachers, and society to address the challenges to minimize learners’ disengagement ratio from schooling.